Rapid method for the determination of moisture content in biodiesel using FTIR spectroscopy - Mirghani, Mohamed E. S.; Kabbashi, Nasreldin A.; Alam, Md. Zahangir; Qudseih, Isam Y. (2010)
A new, rapid, and direct method was developed for the determination of moisture content in biodiesel produced from various types of oils using Fourier transform infrared (FTIR) spectroscopy with Attenuated total reflectance (ATR) element. Samples of biodiesels used in this study were produced using Jatropha curcas oil, sludge palm oil (SPO) and insects’ oil. The calibration set was prepared by spiking double distilled water into dried biodiesel samples in ratios (w/w) between 0 and 10% moisture. Absorbance values from the wavelengths regions 3500 – 3050 cm–1 and 1680 – 1600 cm–1 and partial least square (PLS) regression method were used to derive FTIR spectroscopic calibration model for moisture content in biodiesel samples. The coefficient of determinations (R2) for the models was computed by comparing the results obtained from FTIR spectroscopy against the actual values of the moisture concentrations (%). R2 was 0.9321 and the standard error (SE) of calibration was 1.84. The calibration model were cross validated within the same set of samples and the standard deviation (SD) of the difference for repeatability (SDDr) and accuracy (SDDa) of the FTIR method were determined. With its speed and ease of data manipulation, FTIR spectroscopy is a useful alternative method to wet chemical methods for rapid and routine determination of moisture content in such products for quality control.